The Management of Vacuum-assisted Closure Following Vulvectomy with Skin Grafting - Jun Hu, MD; Hope K. Haefner, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Summary:. Vulvectomies often require removal of large areas of vulvar skin, which may result in problems with wound healing, including infections and scarring. At times, skin grafting is needed following a vulvectomy, and for large excisions, a Foley catheter and rectal tube are often required. Vacuum-assisted closure (VAC) for vulvectomy, with or without skin grafting, has been used for a variety of vulvar conditions. The difficult portion of performing these procedures, with the use of the wound VAC, is obtaining an adequate seal around the Foley catheter and rectal tube. The authors present some useful tips to optimize obtaining and maintaining an adequate seal with the use of Hollister wafers and transparent film dressing during these procedures. This technique has been performed on over 25 patients since 2006. All extensive vulvar wounds requiring split-thickness skin grafts were dressed with a VAC device. With the use of these tips, surgery time and postoperative wound VAC leak alarms have decreased.